2022
DOI: 10.3389/fpain.2022.1022767
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ketamine for comorbid depression and acute or chronic pain: A systematic review

Abstract: Pain and depression frequently co-occur. Due to its antidepressant and analgesic properties, ketamine has been used for the management of treatment-resistant depression and pain. This systematic review examined the literature on the efficacy of sub-anesthetic doses of ketamine in individuals experiencing comorbid depression and chronic pain (CDCP), as well as comorbid depression and acute pain (CDAP). A secondary objective was to provide an assessment of dosage, route, and adverse effects of ketamine treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Although the reported effects of ketamine treatments in military samples were largely convergent with reviews conducted with civilian populations (see 6 , 38 ), there are some nuanced distinctions in effects across mental health outcomes. Specifically, in our sample, we found a moderate-to-large effect for depression ( g = 2.06), which was slightly larger than those found in the Price et al.…”
Section: Discussionmentioning
confidence: 81%
“…Although the reported effects of ketamine treatments in military samples were largely convergent with reviews conducted with civilian populations (see 6 , 38 ), there are some nuanced distinctions in effects across mental health outcomes. Specifically, in our sample, we found a moderate-to-large effect for depression ( g = 2.06), which was slightly larger than those found in the Price et al.…”
Section: Discussionmentioning
confidence: 81%
“…Further studies of various psychosocial interventions for patients with depression in the peri‐operative period would be valuable to inform specific care guidelines. Moreover, as depression becomes an increasingly prevalent issue and is often comorbid with pain, further studies on therapies that target both depression and pain simultaneously are warranted, with some initial promise being shown with ketamine [90].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have reported that CS, depression, and anxiety are related to pain [20][21][22], few studies have directly examined these relationships in patients with poor general mental health. Therefore, we consider it meaningful to evaluate these relationships in patients with poor general mental health.…”
Section: Introductionmentioning
confidence: 99%